When Do Groups Perform Better than Individuals? A Company Takeover Experiment - Marco Casari; Jingjing Zhang; Christine Jackson (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
It is still an open question when groups will perform better than individuals in intellectual tasks. We report that in a company takeover experiment, groups placed better bids than individuals and substantially reduced the winner's curse. This improvement was mostly due to peer pressure over the minority opinion and to group learning. Learning took place from interacting and negotiating consensus with others, not simply from observing their bids. When there was disagreement within a group, what prevailed was not the best proposal but the one of the majority. Groups underperformed with respect to a "truth wins" benchmark although they outperformed individuals deciding in isolation.
Keywords: C91; C92; D03; D81; 330